Clinical photography: attitudes of practitioners specialized in oral mucosal diseases - Olugbeje Helen; Bosco Julia; Lescaille Géraldine; Baaroun Vanessa; Rochefort Juliette (EDP Sciences, 2021)
Introduction: Clinical photography is an important tool for clinical practice, training and research frequently used across medical specialties. It may provide snapshot images of evolving clinical situations. The aim of this work was to record its contribution in the management of oral mucosal diseases and, to identify the methods of using this tool by carrying out a survey with practitioners specialized in oral pathologies. This allowed us to make recommendations for appropriate use of this tool. Material and methods: An online anonymous questionnaire was sent via email, to practitioners who were member of two associations of French specialists. Results: 51 oral medicine specialists completed the survey. Among them, 48 (94%) used photography in their daily practice. Lack of time or interest was the reasons given by the 3 practitioners who did not use photography. Pictures were mostly taken with smartphones, which provide precise and accurate images, and stored on personal or professional computers. Sharing of images was performed mostly by secured professional or personal email addresses. Consent was obtained verbally in most cases. Conclusion: Photography could be a valuable asset in the practice of oral medicine. However, recommendations for the safety of patient personal data are not always followed.